In-house protocol and performance of MALDI-TOF MS in the early diagnosis of bloodstream infections in a fourth-level hospital in Colombia: Jumping to full use of this technology. (December 2020) - Ceballos-Garzón, Andrés; Cabrera, Erika; Cortes-Fraile, Gloria Cecilia; León, Aura; Aguirre-Guataqui, Katherine; Linares-Linares, Melva Y.; Ariza, Beatriz; Valderrama-Beltrán, Sandra; Parra-Giraldo, Claudia M.
Highlights: We applied MALDI-TOF directly to blood cultures to identify bloodstream infections (BSIs). MALDI-TOF allows earlier identification of BSIs and facilitates treatment management. Our protocol requires few steps and has an easily made buffer. Allows better use of robust MALDI TOF technology, with results available in minutes. MALDI-TOF MS is a fast and cheap method for the identification of bacteria. Abstract: Background: Bloodstream infections (BSIs) are a major cause of mortality in hospitalized patients. Rapid diagnosis is crucial because any delay in the antimicrobial treatment is associated with an increase in adverse patient outcomes. The application of matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) technology directly to blood cultures permits earlier identification of BSIs and facilitates treatment management. Methods: A total of 470 positive blood cultures from patient samples were analyzed using Standard Aerobic/F and Anaerobic/F blood culture media. Isolates were identified using conventional identification methods and by the direct method using the MALDI-TOF MS system. Results: In 470 blood cultures, the direct method showed good identification results (420/470, 89%); specifically, accurate species and genus identification in 283/470 (60%), and only correct genus identification in 137/470 (29%). The direct protocol had better performance for Gram-negative compared to Gram-positive bacteria (97% vs 76%) and was unable to identify the positive blood cultures for both yeasts and some bacteria, mostly Gram-positive (50/470). Conclusions: The protocol used here gave good and reliable results, being available up to 24 h earlier, while also leading to better use of MALDI-TOF.